H+-pyrophosphatases enhance low nitrogen stress tolerance in transgenic Arabidopsis and wheat by interacting with a receptor-like protein kinase - Zhang, Huijuan; Chen, Ming; Xu, Chengjie; Liu, Rongbang; Tang, Wensi; Chen, Kai; Zhou, Yongbin; Xu, Zhaoshi; Chen, Jun; Ma, Youzhi; Chen, Weiguo; Sun, Daizhen; et al. (Frontiers in Plant Science, 2023)
Nitrogen is a major abiotic stress that affects plant productivity. Previous studies have shown that plant H+-pyrophosphatases (H+-PPases) enhance plant resistance to low nitrogen stress. However, the molecular mechanism underlying H+-PPase-mediated regulation of plant responses to low nitrogen stress is still unknown. AtAVP1 in Arabidopsis thaliana and EdVP1 in Elymus dahuricus belong to the H+-PPase gene family. In this study, we aimed to investigate the regulatory mechanism of AtAVP1 in response to low nitrogen stress. To this end, we found that transgenic AtAVP1 was more tolerant to low nitrogen stress than was wild type (WT), whereas the avp1-1 mutant was less tolerant to low nitrogen stress than WT. Plant height, root length, aboveground fresh and dry weights, and underground fresh and dry weights of transgenic EdVP1 wheat were considerably higher than those of SHI366 under low nitrogen treatment during the seedling stage. Two consecutive years of low nitrogen tolerance experiments in the field showed that grain yield and number of grains per spike of transgenic EdVP1 wheat were increased compared to those in SHI366, which indicated that EdVP1 conferred low nitrogen stress tolerance in the field. Furthermore, we screened interaction proteins in Arabidopsis; subcellular localization analysis demonstrated that AtAVP1 and Arabidopsis thaliana receptor-like protein kinase (AtRLK) were located on the plasma membrane. Yeast two-hybrid and luciferase complementary imaging assays were used to examine the interactions between AtAVP1 and AtRLK. Results showed that the AtRLK interacted with AtAVP1. Under low nitrogen stress, the Arabidopsis mutants rlk and avp1-1 had the same phenotypes which speculating that AtAVP1 regulates low nitrogen stress responses by interacting with AtRLK in Arabidopsis. Our study provides a novel insight into the regulatory pathway related to H+-pyrophosphatase function in plants.